Number of Bovine Animals in Provinces Incoming Working Field GAP International Agricultural Research and Training Center - Yavuz Han; Galip Bakır; Şahin Tez; Polat İpek (Turkish Journal of Agriculture: Food Science and Technology)
In this review, the share in total and the presence of cattle in provinces of GAPUTAEM has been referred. According to official data of 2012 of TUIK, when number of cattle was 11.972.923 heads in 1991, in 2012 years increased 13.914.912 heads. According to year of 1991, number of cattle increased 16%. In our country, the number of Anatolian Water Buffalo declined from 366.150 heads to 107.435 heads during 1991-2012 and this reduction is 70.6%. 15.977.838 tons milk was obtained from dairy cattle of 5.431.400 heads and average milk yield was 2.942 kg/head. 46.989 tons milk was produced from 46.959 heads of Anatolian Water Buffaloes and average milk yield was 1.006 kg/head. However, there were totally cattle of 1.173.008 heads in study field of Institute. 1.098.895 tons milk was produced from cattle of 451.039 heads. Totally, there were 15.478 heads Anatolian Water Buffaloes in 11 provinces. 6.384 tons milk was produced from 6.738 heads Anatolian Water Buffaloes in 2012. Across the country, despite cattle (domestic) decreased, cattle (cross-bred) and cattle (culture) had increased. The possibility of breeding of native cattle should be investigated. Also, growers and technical staffs should be trained that affected by entering of culture breeds.